1988
DOI: 10.1149/1.2095646
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Segregation of Yttrium in Chromia Scales

Abstract: Implantation of a Co-45 weight percent Cr alloy with a high dose of yttrium causes the oxidation rate of the alloy to decrease by about 100 times at 1000~ in pure oxygen. Also, the mechanism of growth of the Cr203 scale changes from predominant cation diffusion to predominant anion diffusion, both of which occur along grain boundaries in the oxide. Segregation of yttrium ions to grain boundaries in the Cr203 scales has been measured using EDX analysis in a STEM, and the reduction in oxidation rate and the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Evidence for the role of grain-boundary segregation of reactive elements in C r 2 0 3 was given by the experiments [36,37]. STEM measurements revealed that segregation of yttrium at the chromia grain boundaries does indeed occur.…”
Section: Alteration In the Number And Character Of Short-circuit Diffmentioning
confidence: 96%
“…Evidence for the role of grain-boundary segregation of reactive elements in C r 2 0 3 was given by the experiments [36,37]. STEM measurements revealed that segregation of yttrium at the chromia grain boundaries does indeed occur.…”
Section: Alteration In the Number And Character Of Short-circuit Diffmentioning
confidence: 96%
“…Research has shown yttria segregation at the grain boundaries [28]. However, here yttria is homogeneously distributed within the W matrix at atomic level.…”
Section: Importance Of Nano-scale Effects For Understanding the Oxidamentioning
confidence: 78%
“…The fact that small amounts of active elements, such as Y, substantially improve the adherence of oxide scales, was discovered in 1937 [25]. Since then Y has been added to various alloys and studies on the role of Y have been conducted [23,24,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The use of reactive elements, especially rare earths (RE) to improve high temperature oxidation resistance of chromium dioxide and alumina forming alloys is quite well documented. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The improvements are in the form of reduced oxidation rates and increased scale adhesion. The RE can be added to the alloy in elemental form or as oxide dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be applied as an oxide coating to the alloy surface. [3][4][5][6][7]15 Various mechanisms have been proposed to explain the effect of reactive elements in improving oxidation resistance and the most widely accepted mechanism attributes it to segregation of the reactive elements to the interface or to the oxide scale grain boundaries and blocking of Cr ion diffusion though the oxide scale [8][9][10][11] Studies carried out by Seo et al, about the effect of addition of Ce, La and Y to a Fe-22Cr-0.5Mn alloy on the oxidation behavior of the alloy at 800 °C, indicated that Y was the most effective element to reduce the growth rate of the oxide scale. 12 In recent years a number of studies have been carried out to exploit the benefits of rare earth additions on oxidation behavior of chromium dioxide and alumina forming alloys.…”
Section: Introductionmentioning
confidence: 99%